Dall’Alalà funebre all’Appello dei morti (Fiume, dicembre 1920–Milano, dicembre 1921): Nota filologica, tra storia e letteratura - Severino, Valerio (Verbum – Analecta Neolatina, 2021)
The essay aims to examine the links between nationalist literature and political rites in Fascist Italy, by focusing on the poetry of Gabriele D’Annunzio and its exploitation in the aftermath of World War I. As far as the case study of the Alalà formula is concerned, the paper addresses the question of its use in the funerary ceremonies of the Italian Fasces of Combat, as well as its substitution for the national rite of the Appello del caduto, i.e. the ‘Roll Call of the Fallen Soldiers’ in 1921 by the newborn Fascist National Party. On the basis of Italian newspapers, mainly Il Popolo d’Italia, the journal founded by Mussolini, this study provides specific documentary evidence both for this passage from the Alalà to the Roll Call rite and the related political-funerary literature.